2015
DOI: 10.1111/jmg.12129
|View full text |Cite
|
Sign up to set email alerts
|

Petrological and geochronological constraints on lower crust exhumation during Paleoproterozoic (Eburnean) orogeny, NW Ghana, West African Craton

Abstract: New petrological and geochronological data are presented on high-grade ortho-and paragneisses from northwestern Ghana, forming part of the Paleoproterozoic (2.25-2.00 Ga) West African Craton. The study area is located in the interference zone between N-S and NE-SW-trending craton-scale shear zones, formed during the Eburnean orogeny (2.15-2.00 Ga). High-grade metamorphic domains are separated from low-grade greenstone belts by high-strain zones, including early thrusts, extensional detachments and late-stage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 115 publications
(180 reference statements)
5
76
0
Order By: Relevance
“…Although Block et al (2015) highlighted the significance of extension for exhumation in the Bole-Bulenga terrane; they also indicated that extension is certainly not the only process accounting for the exhumation of lower crust. In addition, Sakyi et al (2014) concluded that the oldest pulses of granitic emplacement in the Wa-Lawra belt are around 2212 ± 1 Ma.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although Block et al (2015) highlighted the significance of extension for exhumation in the Bole-Bulenga terrane; they also indicated that extension is certainly not the only process accounting for the exhumation of lower crust. In addition, Sakyi et al (2014) concluded that the oldest pulses of granitic emplacement in the Wa-Lawra belt are around 2212 ± 1 Ma.…”
Section: Introductionmentioning
confidence: 95%
“…According to Block et al (2015), the high grade Bole-Bulenga terrane in North-Western Ghana, is composed mostly of gneisses, metabasites and monzogranites and located between the craton scale N-S Jirapa and the NE-SW Bole-Nangodi shear zones (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The intruded granitoids in the BM domain locally yield ages between 2195 and 2172Ma (Hirdes et al, 1992;Baratoux et al, 2011;Sakyi et al, 2014). Several generations of main magmatic pulses took place later, ranging between 2153 and 2068 Ma (Hirdes et al, 1996;Egal et al, 2002;Gasquet et al, 2003;Baratoux et al, 2011;Block et al, 2015). 10…”
Section: Geological Settingmentioning
confidence: 99%
“…Craton-scale shear zones in NW Ghana (Block et al, 2015; and SW (McFarlane et al, 2016) commonly mark the boundaries between low-grade greenstone belts and high-grade metamorphic rocks of up to amphibolite-migmatite facies.…”
Section: Model Implications For the Ghanaian Sefwi Terranementioning
confidence: 99%
See 1 more Smart Citation